2008
DOI: 10.1373/clinchem.2007.092304
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Methamphetamine and Amphetamine in Human Sweat Following Controlled Oral Methamphetamine Administration

Abstract: BACKGROUND:Understanding methamphetamine (MAMP) and amphetamine (AMP) excretion in sweat is important for interpreting sweat and hair testing results in judicial, workplace, and drug treatment settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
0
25
0
3
Order By: Relevance
“…Various studies now confirm that depuration through induced perspiration may be an effective way to facilitate human clearance of many persistent pollutants from within the body [15, 17, 22]. This study demonstrates, however, that the perfluorinated compounds PFHxS, PFOS, and PFOA are not effectively eliminated in perspiration.…”
Section: Discussionmentioning
confidence: 65%
“…Various studies now confirm that depuration through induced perspiration may be an effective way to facilitate human clearance of many persistent pollutants from within the body [15, 17, 22]. This study demonstrates, however, that the perfluorinated compounds PFHxS, PFOS, and PFOA are not effectively eliminated in perspiration.…”
Section: Discussionmentioning
confidence: 65%
“…Most data are available following a single dose where the detection time is reported to range from 24 to 48 h in plasma to 87 h in urine (177). Limited data are available in relation to repeated doses of methamphetamine, however, the detection time is in the range of 3 days in saliva/oral fluid to 8 days in urine and sweat (177,(179)(180)(181). Accumulation of amphetamines in a keratin matrix is more complex (174) but has been shown to provide a stable measure of temporal exposures with the distribution of drugs along the shaft of the hair expected to reflect historical month-by-month exposures (174).…”
Section: Measurement Of Exposure Using Biological Data (Biomarkers) Gmentioning
confidence: 99%
“…The testing of sweat using sweat patches is a noninvasive method of biomonitoring, however, only a limited number of studies are available that assist in the understanding of methamphetamine and amphetamine excretion in sweat (180,186). Testing conducted with other drugs has identified some uncertainties associated with the method that include potential for time-dependant drug loss due to drug degradation, reabsorption to the skin, volatile losses and contamination on the skin (180,187).…”
Section: Saliva/oral Fluid and Sweatmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily patch usually was the most concentrated 31. In contrast, following methamphetamine administration, cumulative short-term patch concentrations were usually greater than those in the weekly methamphetamine patch 21. Schwilke et al also observed that after controlled codeine administration, the sum of codeine excreted in hourly sweat patches was generally higher than concentrations in the corresponding weekly patch 19.…”
Section: Discussionmentioning
confidence: 99%